MBRS-14. REGULATION OF MEDULLOBLASTOMA IMMUNOGENICITY BY TP53 AND TNF ALPHA. Issue 2 (22nd June 2018) - Garancher, Alexandra; Suzuki, Hiromichi; Ramaswamy, Vijay; Taylor, Michael D; Wechsler-Reya, Robert J
Abstract: Many immunotherapies act by enhancing the ability of T cells to kill tumor cells. But T cell killing depends on recognition of antigens presented by Class I MHC (MHC-I) on the tumor cell surface; if a tumor lacks MHC-I, it cannot be recognized by T cells. To study the efficacy of immunotherapy for Group 3 medulloblastoma, we have used mouse models driven by overexpression of Myc and dominant negative p53 ("MP tumors"), or by overexpression of Myc and Gfi1 ("MG tumors"). While both tumors grow in immunodeficient mice, only MP tumors grow in immunocompetent mice. To understand this difference, we analyzed expression of immunoregulatory molecules, and found that MP tumors completely lack surface MHC-I. Mechanistically, this is because two key proteins required for MHC-I trafficking - TAP1 and ERAP1 - are targets of p53; since MP tumors lack functional p53, they also lack TAP1 and ERAP1, and surface MHC-I. These studies suggest that p53 plays a critical role in determining immunogenicity, and that p53-mutant tumors are resistant to immune attack. To overcome this resistance, we treated tumor cells with agents that regulate MHC-1. We found that low doses of tumor necrosis factor alpha (TNF alpha) can rescue expression of ERAP, TAP and MHC-I on MP tumor cells. In vivo, TNF alpha prolongs survival of tumor-bearing mice, and markedly augments the efficacy of immune checkpoint inhibitors. These results raise the possibility that TNF alpha could be used prior to immunotherapy to render tumors more sensitive to T cell attack.